The implementation of role play teaching technique to improve speaking ability on tenth grade students - Ardeyanti, Dita Indah; Munifatullah, Feni; Nurdiana, Novita (U-Jet Unila Journal of English Language Teaching, 2024)
One of the skill in producing language is speaking, in which the ability itself is essential. Speaking requires a few aspects, this study focused on enhancing students’ fluency, accuracy, pronunciation, and vocabulary. The objective of this study is to improve students’ speaking ability by implementing the Role Play Teaching Technique on 30 students of SMAS Al Kautsar Bandar Lampung. After the pre-test, treatments, and post-test were administered, the results of the tests were compared by using Paired Sample T-test in order to analyze the significant improvement of students’ speaking ability after the implementation of the technique. The research results showed that the technique greatly impacted on students’ speaking ability especially fluency. Further findings such as advantages and disadvantages on the technique are discussed.